2009
DOI: 10.3934/ipi.2009.3.649
|View full text |Cite
|
Sign up to set email alerts
|

A family of inversion formulas in thermoacoustic tomography

Abstract: We present a family of closed form inversion formulas in thermoacoustic tomography in the case of a constant sound speed. The formulas are presented in both time-domain and frequency-domain versions. As special cases, they imply most of the previously known filtered backprojection type formulas.1991 Mathematics Subject Classification. Primary: 92C55, 35L05, 35R30; Secondary: 44A99, 45Q05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 28 publications
(72 reference statements)
0
74
0
Order By: Relevance
“…In [15] it has been shown that for a spherical observation surface in two and three spatial dimensions, the universal back-projection formula can be derived from the inversion formulas of [16,17]. In [32] a class of inversion formulas has been obtained that includes the formulas of [16,17] as well as the universal back-projection formulas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In [15] it has been shown that for a spherical observation surface in two and three spatial dimensions, the universal back-projection formula can be derived from the inversion formulas of [16,17]. In [32] a class of inversion formulas has been obtained that includes the formulas of [16,17] as well as the universal back-projection formulas.…”
Section: Discussionmentioning
confidence: 97%
“…Such formulas are currently only known for special boundaries ∂Ω. For example, explicit inversion formulas have been derived for hyperplanes [5,7,10,13,30,46], spheres [16,17,27,32,46] and cylinders [36]. Reconstruction formulas for some polygons and polyhedra in two and three spatial dimensions have been obtained in [29].…”
Section: Introductionmentioning
confidence: 98%
“…The first is to find closed form inversion formulas for R S . This problem has been solved when S is a sphere, cylinder, hyperplane, or some other special hypersurface; see, e.g., [FPR04,FHR07,Kun07,Ngu09,Pal12,Kun11,Nat12,Pal12,Sal14,Hal14]. The second problem is to find the non-injectivity sets S, i.e., to characterize those hypersurfaces S such that R S ( f ) ≡ 0 does not imply f ≡ 0.…”
Section: Introductionmentioning
confidence: 98%
“…For qualitative photoacoustic tomography, the goal is to form an image of the initial state of the pressure field using boundary measurements of the transient pressure waves. Most of the reconstruction methods assume that the actual pressure field (Dirichlet data) can be measured at the boundary [2,3,4,5,11,22,32,35,36,37,38,42,44,51,52,55,59,60,61,63]. In reality, ultrasound sensors are not able to measure the pressure field directly.…”
mentioning
confidence: 99%